The smallest snowflake - Watts, Bernadette (New York : NorthSouth, 2022)
"Every snowflake has a dream. While the other snowflakes boast about their plans to travel on to glamorous and far off destinations-- the most beautiful mountain in the world or atop the golden pinnacle of the jeweled dome of the castle, St. Basil--the smallest snowflake simply longs for someplace special...someplace warm. The snowflakes fly over oceans, parting wa ys over mountains and red roofed farms, until at last, the smallest snowflake finds her home. And when spring finally arrives with snowdrops and unexpected friendship she knows that she has fulfilled her destiny."--Provided by publisher.
Translation of: Schneeflocke.
Translated from the German.
Keywords: Snowflakes -- Juvenile fiction; Snowflakes -- Fiction; Picture books